Approximating Common Fixed Points of Nearly Asymptotically Nonexpansive Mappings (Analysis in Theory and Applications, 2018)
We use an iteration scheme to approximate common fixed points of nearly asymptotically nonexpansive mappings. We generalize corresponding theorems of [1] to the case of two nearly asymptotically nonexpansive mappings and those of [9] not only to a larger class of mappings but also with better rate of convergence.
Keywords: iteration scheme; nearly asymptotically nonexpansive mapping; rate of convergence; common fixed point; weak and strong convergence.